2018
DOI: 10.1519/jsc.0000000000002781
|View full text |Cite
|
Sign up to set email alerts
|

Very-Short-Duration, Low-Intensity Half-Time Re–warm up Increases Subsequent Intermittent Sprint Performance

Abstract: Yanaoka, T, Hamada, Y, Kashiwabara, K, Kurata, K, Yamamoto, R, Miyashita, M, and Hirose, N. Very-short-duration, low-intensity half-time re–warm up increases subsequent intermittent sprint performance. J Strength Cond Res 32(11): 3258–3266, 2018—This study investigated the effect of very-short-duration, low-intensity half-time re–warm up (RW) on subsequent intermittent sprint performance. Using a randomized cross-over design, 11 healthy men performed 3 trials. In the experimental trials, participants performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 29 publications
2
48
0
Order By: Relevance
“…Of the 14 included studies, seven were described as crossover trials [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ] and five as counter-balanced studies [ 13 , 17 , 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 14 included studies, seven were described as crossover trials [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ] and five as counter-balanced studies [ 13 , 17 , 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study’s samples ranged from 7 to 22 participants (age range: 16–33 years), with a competitive level varying from amateur to elite. Participants were soccer players in seven studies [ 11 , 12 , 16 , 21 , 22 , 23 , 24 ], two studies involved rugby players [ 8 , 13 ], two investigations proposed an intermittent sport-like activity [ 17 , 19 ], and three trials included active people [ 14 , 15 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only 58% of players utilize this strategy because the RW duration of previous protocols exceeds a realistic time frame to be able to implement this strategy ( Towlson et al, 2013 ). A previous study recommended within 3-min RW for practical application ( Towlson et al, 2013 ), and recent studies reported the effectiveness of a 3-min RW on exercise performance ( Yanaoka et al, 2018a , b ; Fashioni et al, 2020 ). To make RW more applicable, it is necessary to develop an RW that players can perform in a short time-frame (within 1 min) of leaving the dressing room and the commencement of the second half.…”
Section: Introductionmentioning
confidence: 99%